2019
DOI: 10.1021/acs.orglett.9b01768
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Oxidation of Thioalkynes To Form Phenylthio Ketene Derivatives via a Noncarbene Route

Abstract: Gold-catalyzed oxidations of thioalkynes with 8-methylquinoline oxides afford 2-phenylthioketenes that can be trapped efficiently with alcohols. The synthetic utility is manifested by terminal and internal thioalkynes over a wide scope, bearing esters, ketones, alkyl, and oxime substituents. Our density functional theory calculations suggest that gold-catalyzed oxidations of terminal and internal thioalkynes with 8-methylquinoline oxides generate gold-bound ketene intermediates without the intermediacy of α-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In 2019, R.-S. Liu reported a 1,2-arylthio migration in the oxidation of thioalkyne substrates (Scheme ). Arylthioketenes AS are generated and subsequently trapped by alcohols to afford the corresponding α-arylthio esters 42 . Various arylthio groups are allowed, and the electronic properties of the aryl group were shown to not significantly influence the reaction outcome.…”
Section: Reactions Without Metal Oxidation State Changementioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, R.-S. Liu reported a 1,2-arylthio migration in the oxidation of thioalkyne substrates (Scheme ). Arylthioketenes AS are generated and subsequently trapped by alcohols to afford the corresponding α-arylthio esters 42 . Various arylthio groups are allowed, and the electronic properties of the aryl group were shown to not significantly influence the reaction outcome.…”
Section: Reactions Without Metal Oxidation State Changementioning
confidence: 99%
“…In 2019, R.-S. Liu reported a 1,2-arylthio migration in the oxidation of thioalkyne substrates (Scheme 23). 72 73 One quinoline molecule is incorporated into the final product, which exhibits two conformers that are stabilized by different hydrogen-bonding interactions. The proposed mechanism entails trapping of the gold carbene by the tethered sulfide to form four-membered sulfonium AT, its subsequent ring opening by residual water to arrive at gold enolate AS, and finally the reaction of the gold O-enolate with another molecule of the oxidant.…”
Section: Reactions Without Metal Oxidation State Change 21 Activated ...mentioning
confidence: 99%
“…The possibility to perform oxidative transformations of alkynyl sulfides in the presence of 8-methylquinoline N-oxide 352 has been studied by Liu and Cheng. 157 It was shown that alkynyl sulfides 351 could be oxidatively rearranged into functionalized ketones 353 when treated with (Ph 3 P)AuCl/ AgNTf 2 in the presence of an excess nucleophile (Scheme 84, part A). On the basis of DFT calculations, it was proposed that the oxidation of 351 does not proceed via the formation of an α-oxo gold carbene, as usually described for related oxidative transformations, but directly via a gold-bound ketene intermediate 354.…”
Section: Alkynyl Sulfides and Selenidesmentioning
confidence: 99%
“…The possibility to perform oxidative transformations of alkynyl sulfides in the presence of 8-methylquinoline N -oxide 352 has been studied by Liu and Cheng . It was shown that alkynyl sulfides 351 could be oxidatively rearranged into functionalized ketones 353 when treated with (Ph 3 P)­AuCl/AgNTf 2 in the presence of an excess nucleophile (Scheme , part A).…”
Section: Carbon π-Systems With Electron-donating Groupsmentioning
confidence: 99%
“…Simultaneously, Liu and coworkers developed [100] gold-catalyzed oxidation of thioalkynes 119 to phenyl/ arylthioketene derivatives using external 8-methylquinoline N-oxides presumably via a noncarbene route (Scheme 72). A wide range of terminal and internal thioalkynes bearing alkyl, ketone, ester, and oxime ether substituents are used.…”
Section: 2-alkyl Aryl Thiol Alkenyl Alkynyl Benzoyloxy or Acylmentioning
confidence: 99%